MODELTERPADU PENGELOLAAN DAERAH ALIRAN SUNGAI (DAS) LIMBOTO - Razak H. Umar (Jurnal Green Growth dan Manajemen Lingkungan, 2012)
AbstractWatershed Conditions (DAS) Limboto has faced seriously problems of highly rates of erosion, sedimentation, spread of critical land, shift functions of forests and rarity quality water of river as a resutt of floods that always happen, water scarcity and the silting up of Lake Limboto. Therefore, the research has conducted as an integral part ofan effort to develop a model ofintegrated watershed management through mechanisms of payments for environment services (PES) and identify institutional forms. Through Valuation Method and Dynamic System ver.2.5 with 84 people of sample is found that preserving watershed area of Limboto will manage by integrated watershed management through the mechanisms of Payments for Environmental Services (PES) has potential to do in light of community participation and willingness to maintain the forest while maintaining the sustainability of the future of Environment and to proven society of social-and economic matters as has showed by analysis ofdynamic systems.